Perancangan Aplikasi Pemesanan Dan Pengeluaran Material Dengan Metode Extreme Programming Berbasis Web - Adi Nugroho, Yoga; Handayani, Ita; Rivaldi Jemadu, Yohanes (CV. Shofanah Media Berkah, 2024)
PT. Niki Four is a general design and build and building maintenance contractor company in Bintaro. These companies really need applications that support and provide public services that satisfy their consumers, applications that help collect data, manage data and provide information easily and quickly. At this time PT. Niki Four inputs goods manually starting from calculating incoming and outgoing goods, so it is possible that during the process there will be errors in recording, inaccurate reports being made and delays in finding the necessary data. For this reason, this research aims to create a web-based application using the Extreme Programming (XP) method which is useful for PT. Niki Four to facilitate data processing in public services and a database design tool in the form of ERD (Entity Relationship Diagram). In software development there are several approaches or methods used, the programming language used is PHP and the database used in building the system is MySQL. In this research the method used is Extreme Programming (XP) to build a public service information system, the design of this information system using the extreme programming (XP) method is the best solution to solve the problems that exist in public services at PT. Niki Four.